2013
DOI: 10.1037/a0031995
|View full text |Cite
|
Sign up to set email alerts
|

Automatic effort mobilization and the principle of resource conservation: One can only prime the possible and justified.

Abstract: Two experiments tested the idea that the principle of resource conservation moderates and limits automaticity effects on effort mobilization. Effort-related cardiovascular response was assessed in cognitive tasks with different levels of task difficulty (Experiment 1) and success incentive (Experiment 2) during which participants were exposed to suboptimally presented action versus inaction primes. As expected, implicit activation of the action concept resulted in stronger effort-related cardiovascular respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 75 publications
6
42
0
Order By: Relevance
“…Thus, trials containing inaction concepts tagged with unpleasant images were appraised as more difficult (i.e., comprising two successive negative signals) and eventually motivated greater force production. This perceived greater difficulty induced by negative affect could therefore reverse the effect of the inaction prime by influencing the mobilization of energy resources (Gendolla, 2012) and hence increase force output , supporting the notion that automatic priming effects on behaviour are context-dependent, moderated by the present task situation and underpinned by boundary conditions (Loersch and Payne, 2011;Silvestrini and Gendolla, 2013;Wheeler and DeMarree, 2009). Such effect on perceived demand was Regressors were aligned to subliminal word presentation.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Thus, trials containing inaction concepts tagged with unpleasant images were appraised as more difficult (i.e., comprising two successive negative signals) and eventually motivated greater force production. This perceived greater difficulty induced by negative affect could therefore reverse the effect of the inaction prime by influencing the mobilization of energy resources (Gendolla, 2012) and hence increase force output , supporting the notion that automatic priming effects on behaviour are context-dependent, moderated by the present task situation and underpinned by boundary conditions (Loersch and Payne, 2011;Silvestrini and Gendolla, 2013;Wheeler and DeMarree, 2009). Such effect on perceived demand was Regressors were aligned to subliminal word presentation.…”
Section: Discussionmentioning
confidence: 71%
“…disappeared. These stimuli presentation durations are similar to those used in other emotion and subliminal word prime experiments (Aarts et al, 2008;Gaillard et al, 2006;Pessiglione et al, 2007;Schmidt et al, 2009;Silvestrini and Gendolla, 2013), adapted for use within an MRI environment and our screen refresh rate constraints.…”
Section: Experimental Design and Proceduresmentioning
confidence: 94%
See 1 more Smart Citation
“…Consistent with our definition of effort mobilization (Kelsey, 2012), PEP is thought to reflect the sympathetic effects on the heart, mediated by its beta-adrenergic receptors, and has been shown to respond proportionally to task engagement (Richter et al, 2008). Further, research has shown that PEP becomes progressively shorter in response to increasing task difficulty (Richter et al, 2008;Silvestrini & Gendolla, 2013). It is important to note that these effects of decreased PEP were observed in the absence of a decrease in heart rate.…”
Section: Introductionmentioning
confidence: 71%
“…According to the energy conservation principle (Richter 2015;Silvestrini and Gendolla 2013), people are motivated to conserve effort. For example, when performing a task people do not expend more effort than is necessary and worthwhile to successfully complete the task (motivational intensity theory, Brehm and Self 1989;Wright 1996).…”
Section: Depletion and Use Of Mental Contrastingmentioning
confidence: 99%